An equivalent discontinuous modeling method of jointed rock masses for DEM simulation of mining-induced rock movements. (August 2018) - Regassa, Bayisa; Xu, Nengxiong; Mei, Gang
Abstract: The Discrete Element Method (DEM) is of obvious and inherent advantages in simulating large displacements and discontinuous deformations of rock masses, and thus is suitable to simulate the mining-induced rock movements. However, when the region of the DEM calculation model is large, for example, when both the length and width of the research area are larger than several hundreds of meters, the rock mass in the model range often contains a large number of actual joints. If the calculation model is built according to the distribution of the actual joints, the calculation model of DEM will consist of a large number of blocks, which would lead to the impossibility of numerical calculations. To address this problem, an Equivalent Discontinuous Modeling Method (EDMM) of jointed rock masses for DEM simulation of mining-induced rock movements is proposed in this paper. In this method, an actual geological body with a complex joint system will be simplified into an Equivalent Discontinuous Model (EDM), which is a DEM calculation model with a simple hypothesis joint system. The approach for determining the mechanical parameters, i.e., the cohesive strength ( C ), the internal friction angle ( ϕ ), the joint normal stiffness (JKN), and the joint shear stiffness (JKS), of the hypothetical joints of the EDM is the core of the proposed EDMM. The main procedure of the proposed EDMM is composed of: (1) for each subarea of an EDM, building a group of Equivalent Discontinuous Cube Models (EDCMs) that are of different joint spacings; (2) determining the joint mechanical parameters of each EDCM based on the mechanical properties of the actual rock masses of the subarea; (3) establishing the relationships between the joint spacings and joint mechanical parameters for each subarea of EDM; and (4) determining the mechanical parameters of the hypothesis joints in each subarea of the EDM according to these relationships. By exploiting the EDM, the DEM numerical simulation is performed to simulate the mining-induced rock movements and failures. To demonstrate the applicability, the proposed EDMM was employed to simulate the rock movements and failures triggered by mining under the western open-pit final slope of Yanqianshan iron mine.